Transposed poisson structures on low dimensional quasi-filiform Lie Algebras of maximum length - Sapar, Siti Hasana; Saydaliyev, Azamat; Deraman, Fatanah; Abdurasulov, K. (Pleiades Publishing, 2025)
The article first computes 1/2 -derivations of five and six dimensional quasi-filiform Lie algebras of maximum length. Then, it constructs non-trivial transposed Poisson algebras using these 1/2 -derivations of quasi-filiform Lie algebras of maximum length. We have also established commutative associative multiplication to build a transposed Poisson algebra associated with a given Lie algebra.